Efficacy of the cigarette-burning application combined with medication intervention for smoking cessation in China: A randomized controlled trial - Xiao-Wen Wei; Rui Qin; Yong-Zhuang Liu; Zhao Liu; An-Qi Cheng; Xin-Mei Zhou; Zheng Su; Zi-Yang Cui; Jin-Xuan Li; Liang Zhao; Dan Xiao; Chen Wang (Digital Health)
Background Although smartphone application for smoking cessation was considered a promising strategy, there were scarce studies on the combination of usual interventions and apps for smoking cessation in China. Our study aimed to evaluate the efficacy of the Cigarette-Burning application combined with medication intervention for smoking cessation. Methods A parallel, open-label randomized clinical trial was conducted with a ratio of 1:1 allocation into the bupropion plus app group and bupropion group. All participants received bupropion intervention. Besides, participants in the bupropion plus app group were required to download and use the Cigarette-Burning app. Follow-up visits were conducted at weeks 1, 2, 4, 9, 12, and 24 after initiation of treatment. Results Four hundred participants were eventually included and analyzed from July 2019 to June 2021. The continuous abstinence rate at 9–12 weeks was significantly higher in the bupropion plus app group (39.5%) than in the bupropion group (27.5%) (OR = 1.64, 95% CI: 1.04–2.60, p  < .05). The similar result was found for the 24-week sustained abstinence rate. The results of subgroup analysis expressed that the 9–12 weeks continuous abstinence rate in the bupropion plus app group was significantly higher than the bupropion group when the age of participants ≥ 50, the education level was college and above, FTND scores > 5, age at starting smoking ≤ 18 ( p  < .05). Conclusions Our study found that the intervention combined with the Cigarette-Burning smartphone application is more effective than medication alone, and the application for smoking cessation could be an accessible complement to smoking cessation medication treatment.